Current Status of New Anticoagulants in the Management of Venous Thromboembolism - Roberto C. Montoya; Ajeet Gajra (Advances in Hematology)
Venous Thromboembolism, manifested as deep venous thrombosis and pulmonary embolism, is a common problem associated with significant morbidity, mortality, and resource expenditure. Unfractionated heparin, low-molecular-weight heparin, and vitamin K antagonists are the most common treatment and prophylaxis, and have demonstrated their efficacy in a vast number of previous studies. Despite their broad use, these agents have important limitations that have led to the development of new drugs in a bid to overcome the disadvantages of the old ones without decreasing their therapeutic effect. These novel medications, some approved and others in different stages of development, include direct thrombin inhibitors like dabigatran etexilate, and direct activated factor X inhibitors like rivaroxaban. The current paper will review the characteristics, clinical trial results, and current and potential therapeutic uses of these new agents with a focus on the categories of direct thrombin inhibitors and activated factor X inhibitors.